E0533 The effect of QCA in left main lesion. (17th November 2010) - Qing, Qin; Juying, Qian; Bin, Fan; Qibin, Wang; Lei, Ge; Junbo, Ge
Abstract : Objective: Using Intravascular ultrasound (IVUS) as a standard to evaluate the ability of Quantitative Coronary Angiography (QCA) in judging the lumen diameter before and after percutaneous coronary intervention (PCI) in left main lesion, in choosing stent before PCI and also in evaluating the effect of PCI. Method: A retrospective study was conducted including left main lesion completing IVUS study which either has a diameter stenosis exceeding 50% by visual measure or a dissection confirmed by coronary angiography (CAG) in the past 4 yrs. CAAS was used in analysing CAG data and the extent of left main lesion was measured in a position with best exposure of left main coronary artery (cranial or caudal). Echoplaque was used to analyse IVUS data. Result: From June 2004 to December 2008, sixty-four patients met the inclusion criteria including 49 males (76%) with an average age of 61.2±11.2 years old. In all the lesions underwent IVUS study, there are 18 ostial lesions, 8 trunk lesions, 17 distal lesions without bifurcation involvement, 7 distal lesions with either LAD or LCX involved, 7 distal lesions with both LAD and LCX involved, 11 diffuse lesions and 2 cases of left main dissection. Of them, 6 patients had two sites of lesions. Fifteen patients were not able to complete QCA study before the PCI procedure and the relevant lesions including one case of ostial lesion, 6 cases of distal lesion with bifurcation involved and 8 cases of diffuse lesion. Before PCI, the average minimum lumen diameter analysed by QCA and IVUS was 1.50±0.73 mm, 1.82±0.59 mm respectively; reference lumen diameter was 4.02±0.71 mm, 3.74±0.63 mm separately. After PCI, the average minimum in-stent lumen diameter by QCA and IVUS was 3.75±0.53 mm, 3.25±0.66 mm; and the reference lumen diameter was 4.06±0.49 mm, 3.77±0.60 mm respectively. Relative analysis showed the correlation coefficient of minimum lumen diameter and reference lumen diameter before PCI, minimum in-stent lumen diameter and reference lumen diameter after PCI was 0.72 (p<0.001), 0.47 (p<0.05), 0.73 (p<0.001), 0.79 (p<0.001), respectively. Conclusion: QCA has a high correlation with IVUS measurement and can be used in guiding and evaluating PCI procedure of left main disease. However, its use is limited in diffuse lesion and distal lesion involving bifurcation of left main coronary artery and a high quality CAG image is required.